PS 11-55 CORRELATION RELATIONSHIP HOMA INDEX WITH BLOOD PRESSURE, HEART RATE AND LIPID IN PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC SYNDROME WITHOUT DIABETES TREATED DIFFERENT BETA BLOCKERS. (September 2016) - Rekovets, Oksana; Sirenko, Yuriy; Torbas, Olena; Mironova, Olga; Primak, Galina; Vashchylko, Alla; Pavlyuk, Evgenia; Savitskiy, Sergey; Granich, Vladimir; Sidorenko, Petro; Polishchuk, Sergey
Abstract : Objective: The aim. Correlation relationship HOMA index for treatment different beta blockers in patients with metabolic syndrome (MS) without diabetes and mild to moderate arterial hypertension (AH). Design and Method: 131 patients were included (71-men, 60-women). SBP and DBP, HR, ABMP, glucose tolerance test, HOMA were done in all patients before and 6 month after of therapy. 1-st group (n-32) patients was treated by atenolol 50–100 mg per day, 2-nd group (n-35) - nebivolol 5 mg per day, 3-d group (n-32) - carvedilol 25–50 mg per day, 4-th group (n-32) - bisoprolol 5–10 mg per day. Results: Office BP, HR, ABMP, equally decreased in all group therapy. In nebivolol delta HOMA correlation with office DBP before r = 0, 431, p = 0, 011. HOMA before correlated with HR24 before r = 0, 364, p = 0, 032. HOMA after correlated with cholesterol after r = −0, 378, p = 0, 028, with LDL cholesterol r = −0, 355, p = 0, 039. In carvedilol delta HOMA had no correlation, HOMA after correlated with TG before r = 0, 381, p = 0, 032, VLDL cholesterol before r = 0, 357, p = 0, 045. Women in carvedilol correlation with office SBP r = 0, 354, p = 0, 047, DBP r = 0, 427, p = 0, 016, HR - r = 0, 354, p = 0, 047 after treatment. In bisoprolol delta HOMA correlation with cholesterol before r = −0, 387, p = 0, 029. HOMA after correlated with family history of hypertension r = −0, 393, p = 0, 026. In atenolol delta HOMA had no correlation. HOMA before atenolol correlated with family history of hypertension r = 0, 352, p = 0, 048, BMI r = 0, 496, p = 0, 006. Conclusions: If patients with AH and MS without DM and has family history of diabetes mellitus and higher BMI not recommend treatment of atenolol. If patients has family history of AH recommend treatment bisoprolol. BP better decreased in women than men in carvedilol group. The higher the office DBP before treatment, the better the HOMA decreased after treatment with nebivolol.